Comparative study of physical fitness and physiological parameters between deaf/dumb and blind students of Amravati University - Khan, Mohammad Ashraf; Jose, Tomy (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2021)
The purpose of the study was to find out the study of physical fitness and physiological parameters between deaf/dumb and blind students of Amravati University. For the present study the source of subjects were selected from the deaf/dumb and blind schools of Amravati University. Eighty (80) students were selected as the subjects from deaf/dumb and blind schools of Amravati University. 40 students were selected from deaf/dumb and 40 from blind schools of Amravati University. The subjects were selected by using simple random sampling method. In this study comparison of two physical variables strength and flexibility and two physiological variables fat percentage and exhale capacity were taken into consideration from both deaf/dumb and blind students of Amravati University. For the present study data pertaining to various physical and physiological variables were be collected through the administration of various tests. The data for the study is to be collected and statistical analysis and interpretation of data were be done by using statistical technique ‘t’ test because only two groups are considered one group from deaf/dumb population from various deaf/dumb schools of Amravati University and other group from blind section of the various schools of Amravati University.